Cross-adaptation to cadmium stress in Plantago ovata by pre-exposure to low dose of gamma rays: Effects on metallothionein and metal content. (August 2015) - Ghoshal, Nirmalya; Talapatra, Shonima; Talukder, Pratik; Sengupta, Mandar; Ray, Suman Kumar; Chakraborty, Anindita; Raychaudhuri, Sarmistha Sen
Abstract Purpose: To investigate the effects of gamma pre-exposure on cadmium accumulation in Plantago ovata seedlings. Metallothionein (MT) localization was also studied following Cadmium (Cd) treatment in P. ovata. Materials and methods: DNA damage was determined by alkaline comet assay. MT gene and protein expression were studied by real-time polymerase chain reaction and flow cytometry, respectively, in root and shoot tissues. Metal accumulation (Cd, zinc [Zn], iron [Fe]) was evaluated by Atomic Absorption Spectroscopy. Results: Cd treatment decreased seed germination rate, biomass and free radical scavenging activity and increased DNA damage in a dose-dependent manner. When P. ovata seeds were pre- exposed to 5 Gy gamma dose (prior to Cd treatment) seed germination rate, biomass and free radical scavenging activity increased significantly. MT genes (PoMT1, PoMT2 and PoMT3) and MT protein expression enhanced when 5 Gy gamma-irradiated seeds were grown in Cd containing medium and Cd accumulation also increased in a dose-dependent manner. Conclusions: Higher Cd accumulation in P. ovata seedlings may be attributed to the upregulation of PoMT genes in gamma pretreated seedlings. Localization of metallothionein in cytosol and nucleus indicated its positive role against Cd-mediated cytotoxic and genotoxic effects.